2007 American Control Conference 2007
DOI: 10.1109/acc.2007.4282491
|View full text |Cite
|
Sign up to set email alerts
|

Robust Tracking Control for a Piezoelectric Actuator

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Abstract: In this paper, a hysteresis model-based nonlinear robust controller is developed for a piezoelectric actuator, utilizing a Lyapunov-based stability analysis, which ensures that a desired displacement trajectory is accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…When the whole S&A structures are assembled, it will be sealed, which could result in the designed microactuators have a non-contact with the driven parts. Further, by investigating their advantages and disadvantages of the existing driving types, combined with the S&A device's requirements, a miniature disksucker-type micro-driving prototype using electromagnet was chosen, and the sheet structure manufactured with soft magnetic body material is selected as the magnet materials for locking pin and slider [8,9,10] .…”
Section: Icemi'2009mentioning
confidence: 99%
“…When the whole S&A structures are assembled, it will be sealed, which could result in the designed microactuators have a non-contact with the driven parts. Further, by investigating their advantages and disadvantages of the existing driving types, combined with the S&A device's requirements, a miniature disksucker-type micro-driving prototype using electromagnet was chosen, and the sheet structure manufactured with soft magnetic body material is selected as the magnet materials for locking pin and slider [8,9,10] .…”
Section: Icemi'2009mentioning
confidence: 99%
“…There are also a few different control methods which show controllers leading to improvements in speed and accuracy; see [10,11]. This paper builds on the robust feedback control approach used in [12][13][14] in which the control of hysteresis in a piezoelectric actuator is adopted from the charge control method, which can be found in [15,16]. In [15,16], it is shown that the use of charge control can lead to reduced hysteresis in a piezoelectric actuator.…”
Section: Introductionmentioning
confidence: 99%
“…The control method used in our approach to achieve our aims in terms of the scanning speed and the quality of images on the AFM can be summarized in three major features as compared to the previous approaches. [1][2][3][4][5][6][7][8][9][10][11][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary version of this paper has appeared in the proceedings of the American Control Conference, New York, NY, USA, 2007 [49].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Let P(z, t) ∈ R denote the following non-negative function P 1 2 e 2 + 1 2 mr 2 (49) Note that the right-hand side of (49) can be bounded as follows…”
Section: Appendix 2: Proof Of Theoremmentioning
confidence: 99%